Cryptanalysis of a hybrid-structured onion routing scheme - Long-hai LI; Shao-feng FU; Rui-dan SU; Xiang-quan CHE (Tongxin xuebao)
SHI Jin-qiao et al's hybrid-structured onion routing scheme was analysed and some security flaws were found in their design.The first flaw was derived from the malleability of its cryptographic message format which could be exploited by attackers to redirect an onion message or embed tags into it for tracing its routing path.The second flaw was the vulnerability of relay servers to chosen ciphertext attack.Three different attacks were presented that each broke the sender-receiver unlinkability entirely at a relatively low co To evade these attacks,a modified scheme was also proposed which could capture malicious nodes by using upstream investigation.